Green Accounting: Penerapan Pentuple Bottom Line pada Industri Pengolahan Rumput Laut menuju Sustainability Development - Fadlilah, Miftah; Alam, Syamsu; Tenriwaru, Tenriwaru (JOM, 2024)
This study aims to see the implementation of the Pentuple Bottom Line in seaweed processing industry companies to realize sustainable development. This study is a qualitative study with an interpretive paradigm to see and examine more deeply the implementation of the Pentuple Bottom Line (profit, people, planet, phenotechnology, and prophet) at PT. Bantimurung Indah Maros. The results of the study are that PT. Bantimurung Indah has implemented the five aspects that are indicators of the Pentuple Bottom Line. However, no accountability report is produced for reporting purposes to stakeholders, all of which are still in the form of activities and have not been stated in a particular post in the report. As an industrial company, in addition to being profit-oriented, PT. Bantimurung Indah still pays attention to social aspects, such as assistance with facilities and infrastructure to the surrounding community and environmental aspects (planet), such as tree planting and waste management. PT. Bantimurung Indah also realizes the importance of the phenotechnology aspect with the use of technology in the production process and the prophet aspect related to transcendental awareness. PT. Bantimurung Indah Maros is expected to report its environmental costs in detail to meet the needs of stakeholders. The disclosure can be proposed for preparing a written sustainability report to be more transparent to all parties.